A Market Expansion Approach for “Thiptawan Cereal Drinks” by Ban Khuan-Pom’s Brown Rice Community Enterprise, Phatthalung Province - Thongpoon, Siriluck; Wangbenmad, Chutima; Nhunchek, Khanungnit; Thongpoon, Kumpee; Boonrotpong, Boottree; Prommontree, Jutamas (Journal of Community Development Research (Humanities and Social Sciences); Vol 11 No 3 (2561): July-September 2018DO - 10.14456/jcdr-hs.2018.5, 2018)
การวิจัยนี้เป็นการวิจัยเชิงคุณภาพมีวัตถุประสงค์เพื่อศึกษาบริบทการดำเนินงานและแนวทางในการขยายตลาดของผลิตภัณฑ์เครื่องดื่มธัญพืชทิพย์ตะวันของวิสาหกิจชุมชนข้าวซ้อมมือบ้านควนปอม จังหวัดพัทลุง ใช้แบบสำรวจ แบบสัมภาษณ์ การสังเกตและการประชุมกลุ่มย่อยในการรวบรวมข้อมูลจากกลุ่มตัวอย่างซึ่งเป็นสมาชิกวิสาหกิจชุมชนข้าวซ้อมมือบ้านควนปอม เจ้าหน้าที่ภาครัฐ และตัวแทนจัดจำหน่าย รวม 35 คน ผลการศึกษา พบว่า วิสาหกิจชุมชนนี้มีการจัดการทรัพยากรความรู้และภูมิปัญญาชุมชนในกระบวนการผลิตมีจุดเด่นในการนำข้าวสังข์หยดอินทรีย์ GAP มาใช้เป็นวัตถุดิบหลักของผลิตภัณฑ์ แต่ยังมีข้อจำกัดด้านการตลาดและการคำนวณต้นทุนสินค้าไม่ครบถ้วน ดังนั้น การนำแนวทางด้านการขยายตลาดโดยการเจาะตลาดเดิมเพื่อให้สินค้าเป็นที่รู้จักแก่ผู้บริโภคมากขึ้น และการพัฒนาตลาดเพื่อเป็นการเพิ่มยอดขายและขยายฐานการตลาดให้ผู้บริโภครับรู้ในวงที่กว้างขึ้นด้วยการเพิ่มช่องทางการจำหน่าย การสรรหาตัวแทนขาย การเพิ่มความหลากหลายของขนาดบรรจุภัณฑ์ การปรับปรุงกลยุทธ์การขาย การประชาสัมพันธ์ การปรับราคาให้เหมาะสม การจัดแสดงสินค้า การทดลองชิม และการพัฒนาช่องทางจำหน่ายออนไลน์ ซึ่งแนวทางนี้จะช่วยให้วิสาหกิจชุมชนสามารถเติบโตสร้างมูลค่าเพิ่มทั้งทางด้านเศรษฐกิจและสังคมต่อชุมชนและประเทศชาติ คำสำคัญ: แนวทางการขยายตลาด  ห่วงโซ่  คุณค่าเครื่องดื่มธัญพืช  วิสาหกิจชุมชนข้าวซ้อมมือบ้านควนปอม      This qualitative research was conducted to study the operational contexts and possibility of market expansion for ‘Thiptawan Cereal Drink’, a product from Ban Khuan-Pom’s Brown Rice Community Enterprise in the province of Phatthalung. Data was collected using surveys, interviews, observations and focus groups with 35 subjects from members of this community enterprise, government agencies and distributors. The results revealed that this enterprise applied its resources, knowledge and local wisdom throughout the production process. Its value was GAP of Sangyod Brown Rice which was key ingredient. However, the enterprise faced with market limitation including production cost analysis. Therefore, a market expansion approach with both market penetration and market development was proposed. They were increasing distributors, recruiting salespeople, varying product and packaging sizes, exploring new sales strategies, improving public relations, adjusting suitable price, displaying products, sensory testing and developing online channel. This approach has the potential to benefit this community and the nation through the expected economic and social growth of the enterprise resulting from these forms of expansion. Keywords:  Market Expansion Approach, Value Chain, Cereal Drinks, Ban Khuan-Pom’s Brown Rice Community Enterprise